Utilization of oil palm fronds into biochar to support sustainable soil improvement - Sandria, Feri; Sinaga, Novalia Siti Ramadani; Zamzami, Lutfi Fadilah (Universiti Teknologi MARA Cawangan Johor Kampus Pasir Gudang, 2025)
The utilization of oil palm frond waste as raw material for biochar production is a sustainable innovation in supporting environmentally friendly agriculture. Oil palm fronds are one of the abundant agricultural wastes in oil palm plantations that come from maintenance in the form of pruning oil palm fronds. Palm fronds contain lignin, cellulose and hemicellulose which can be used as raw materials for making activated carbon. Its utilization as biochar offers a sustainable solution to improve soil quality and reduce agricultural waste. Biochar contains carbon, oxygen, hydrogen, and organic ash. This research focuses on the conversion of oil palm fronds into biochar through pyrolysis process and evaluates its potential as a soil improver to improve fertility, structure, and water storage capacity. The results showed that palm frond biochar is effective in increasing soil organic carbon content, improving nutrient retention, and reducing dependence on synthetic fertilizers, as well as reducing global warming. In addition, its use also supports sustainable plantation management by minimizing waste and supporting a circular economy. This research emphasizes the importance of integrating biochar technology in agricultural practices to achieve long-term environmental and economic sustainability.